Aplikasi Absensi dan Penjadwalan Berbasis Web di SMA Negeri 1 Pelaihari menggunakan framework Laravel - Nur Maida; Veri Julianto (Fakultas Sains Dan Teknologi Universitas Islam Asyafiiyah, 2024)
Pelaihari 1 Public High School, located in Pelaihari District, is one of the educational institutions that supports improving the quality of education. Providing information by students is carried out by collecting the necessary data, then the data is input using Microsoft Excel or Microsoft Word. Apart from that, paper is also used when making attendance. Any existing data is then shared back with teachers and students who need it via WhatsApp. This method is considered less effective due to limited program functions, easy file loss, difficulty in searching for data, and also in terms of time. Therefore, a Web-Based Attendance and Scheduling Application was developed at SMA Negeri 1 Pelaihari using the Laravel Framework. This application is expected to fulfill one of the Admin's tasks in managing data, so that Admins feel it is easier to share information with teachers and students. The features contained in this system include class data, student data, employee data, subject data, schedule data, User data, attendance data, reporting and journal data. This system was developed using a prototype development model, the Laravel framework, and was designed using the Unified Modeling Language (UML) and Entity Relationship Diagram (ERD) models. The programming language used is PHP and the database used is MySQL.